2021
DOI: 10.1016/j.fertnstert.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing definitions and reporting guidelines for the infertility core outcome set: an international consensus development study

Abstract: a face-to-face consensus development meeting, which agreed consensus definitions. A standardized approach to reporting was also developed as part of the process. Participants/Materials, Setting, Methods: Healthcare professionals, researchers, and people with fertility problems were brought together in an open and transparent process using formal consensus development methods. Main Results and the Role of Chance: Forty-four potential definitions were inventoried across four definition development initiatives, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…To address inconsistencies in outcome reporting across male and female infertility trials, an international working group of healthcare professionals and researchers have developed the Core Outcome Measures for Infertility Trials (COMMIT) initiative ( Core Outcomes in Women's and Newborn Health Initiative, 2014 ). This initiative will develop stakeholder-driven development of core outcome sets relevant to clinicians, researchers, and patients and has developed a consensus strategy for reporting core outcomes and standardizing their definitions ( Duffy et al , 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address inconsistencies in outcome reporting across male and female infertility trials, an international working group of healthcare professionals and researchers have developed the Core Outcome Measures for Infertility Trials (COMMIT) initiative ( Core Outcomes in Women's and Newborn Health Initiative, 2014 ). This initiative will develop stakeholder-driven development of core outcome sets relevant to clinicians, researchers, and patients and has developed a consensus strategy for reporting core outcomes and standardizing their definitions ( Duffy et al , 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, live birth rate per embryo transfer has been reported as the success rates of IVF/ICSI [ 37 ]. However, embryo freezing and thawing becomes increasingly universal that live birth rate of a single embryo transfer cycle is not adequate to evaluate the effect of the IVF/ICSI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of the outcomes given by the authors of each study was extracted to evaluate the possible heterogeneity derived from different classifications. For the studies not stating definitions, outcomes were identified according to the guide for the standardization of definitions and reports in infertility ( 24 ). All reviewers extracted the data independently and in duplicate and disagreements were solved by consensus or intervention of a third reviewer.…”
Section: Methodsmentioning
confidence: 99%